Respuesta :

Answer:

-3+2sqrt7

-3-2sqrt7

Step-by-step explanation:

x^2+6x-9=10

x^2+6x-9-10=0

x^2+6x-19=0

ax^2+bx+c=0

a=1 b=6 c=-19

As cannot be solved by completing square we will use quadratic equation

x= (-b+sqrt(b^2-4ac))/2a     and      x= (-b-sqrt(b^2-4ac))/2a

x= (-6+sqrt(6^2-4*-19))/2     and      x= (-6-sqrt(6^2-4*-19))/2

x=(-6+sqrt(36+76))/2           and      x=(-6-sqrt(36+76))/2

x=(-6+4sqrt7)/2                   and       x=(-6-4sqrt7)/2

x=(-3+2sqrt7)                       and      x=(-3-2sqrt7)

x=2.29                                 and      x= -8.29